Electron Spin Relaxation of Tb(3+) and Tm(3+) Ions - McPeak, Joseph (Appl Magn Reson, 2020)
Electron spin relaxation times T(1) and T(m) of Tb(3+) and Tm(3+) in 1:1 water:ethanol and of Tb(3+) doped (2%) in crystalline La(2)(oxalate)(3) decahydrate were measured between about 4.2 and 10 K. Both cations are non-Kramers ions and have J = 6 ground states. Echo-detected spectra are compared with CW spectra and with field-stepped direct-detected EPR spectra. Due to the strong temperature dependence of T(1), measurements were not made above 10 K. Between about 4.2 and 6 K T(1) is strongly concentration dependent between 1 and ~50 mM. T(1) values at 4.2 K are in the μs range which is orders of magnitude faster than for 3d transition metals. Phase memory times, T(m), are less than 500 ns, which is short relative to values observed for 3d transition metals and organic radicals at 4 K. T(m) is longer in the oxalate lattice which is attributed to the lower proton concentration in oxalate than in the organic solvent, which decreases nuclear spin diffusion. The rigidity of the crystalline lattice also may contribute to longer T(m).